Application of the project management methodology synthesis method with fuzzy input data - Kononenko, Igor; Aghaee, Ahmad; Lutsenko, Svetlana (Eastern-European Journal of Enterprise Technologies, 2016)
The definition of a “project management methodology” is clarified. A method of the project management methodology synthesis for a particular project with fuzzy input data is proposed. The method involves the development of a generalized project management methodology. Based on the information presented in the generalized methodology, an expert or a group of experts selects policies, rules, procedures , practices, life cycle and organizational structure of a particular project, assign roles and responsibilities in the project. The experts have the opportunity to set several combinations of the generalized methodology components, which are the most relevant to the project. The problem of selecting the best methodology for a particular project is solved according to the criteria of complexity , cost of management operations and associated risks. Optimization is carried out with the fuzzy input data. The operation of the given method is shown on the example of the project on the “PTCQR ProjectScopeOptimization” software development for project scope optimization.